Formulation of zein nanoparticles for augmenting the anti-inflammatory activity of dexketoprofen - El Hassab, Mahmoud A.; Ibrahim, Mona H.; Abdel Mageed, Sherif S.; Mahmoud, Abdulla M. A.; Othman Ahmed, Zainab Sabry; Mosallam, Shaimaa; Abdelbari, Manar Adel; Khaleel, Eman F.; El Hasab, Maram A.; Elsayyad, Asmaa; Allam, Shady; Eltabeeb, Moaz A.; et al. (Frontiers in Pharmacology, 2025)
IntroductionTopical delivery of anti-inflammatory drugs is an important strategy for enhancing therapeutic efficacy while minimizing systemic side effects. This study focuses on improving the anti-inflammatory activity of Dexketoprofen by developing zein nanoparticles (ZNs) as a novel topical carrier system, aiming to optimize drug delivery and patient outcomes.MethodsDexketoprofen-loaded ZNs were prepared using an ethanol injection technique and optimized via a 23 full factorial design. The effects of three variables—phosphatidylcholine (PC) amount (X1), type of surface-active agent (SAA, X2), and SAA amount (X3)—were evaluated on entrapment efficiency (EE%), particle size (PS), polydispersity index (PDI), and zeta potential (ZP). Design-Expert® software was employed to identify the optimal formulation. Additionally, molecular docking studies were performed to explore interactions between Dexketoprofen and formulation components. The selected formulation (F7) was further characterized for morphology using scanning electron microscopy. In vivo efficacy was assessed using a formalin-induced paw edema model in rats, and histopathological analysis was conducted to evaluate skin irritation potential.ResultsThe optimal formulation (F7), prepared with 200 mg PC and 20 mg Pluronic F127, demonstrated an entrapment efficiency of 92.44 ± 7.21%, particle size of 91.88 ± 3.01 nm, PDI of 0.42 ± 0.02, and zeta potential of −24.10 ± 0.29 mV. F7 exhibited a smooth, spherical morphology. In vivo studies revealed significantly enhanced anti-inflammatory activity compared to free Dexketoprofen. Histopathological examination confirmed the non-irritant nature of the formulated ZNs on rat skin.DiscussionThese findings highlight the effectiveness of zein nanoparticles as a promising topical delivery system for Dexketoprofen. The optimized ZNs not only improved drug entrapment and stability but also provided superior anti-inflammatory efficacy and excellent skin tolerability, suggesting their potential for the treatment of inflammatory skin conditions.